The influence of organizational technology strategy on sustaining ethical business strategies for shariah compliant micro finance institutions in Indonesia - Abadi, Kurnia Rahman; Mhd. Sarif, Suhaimi (2018)
Organizational technology strategy as functional strategy has moderating role in sustaining ethical business strategies formulation and implementation. An organization with Shariah compliant credential optimizes all capability to sustain competitiveness and performance. This research was conducted to establish the relationship between business strategies towards corporate governance practices and structures, incorporated by organizational capacity elements and information technology strategy of Islamic micro finance institutions in Indonesia. Because of poor corporate governance, which led to a decline in public trust and also equity market values per share during the financial crisis, 1997-1998, the issue of corporate governance has become a major concern of stakeholders.